1991
DOI: 10.1111/j.1365-2133.1991.tb00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in human hair growth

Abstract: Various parameters of hair growth were determined every 28 days for 18 months in 14 healthy Caucasian men aged 18-39 with indoor occupations in Sheffield, U.K. (latitude 53.4 degrees N). In the scalp the proportion of follicles in anagen reached a single peak of over 90% in March, and fell steadily to a trough in September. The number of shed hairs reached a peak around August/September, when least follicles were in anagen. At this time the average loss of hairs was about 60 per day, more than double that duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
3
5

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(131 citation statements)
references
References 17 publications
9
114
3
5
Order By: Relevance
“…We did not observe the seasonal variations other authors have found in adults [4, 5, 6]. As far as we know, no data are available for children.…”
Section: Discussionmentioning
confidence: 37%
“…We did not observe the seasonal variations other authors have found in adults [4, 5, 6]. As far as we know, no data are available for children.…”
Section: Discussionmentioning
confidence: 37%
“…These results confirm the findings of authors who have formerly demonstrated seasonal changes in human hair growth, though this is the first study performed systematically in women: Orentreich [19] reported 3 women in New York who experienced maximum hair loss in November. By studying a group of 14 men during 18 months, Randall and Ebling [20] showed that the proportions of telogen hair and of hair shedding were maximal in September. Courtois et al [21] observed 10 men, with or without alopecia, for a period of between 8 and 14 years, and also demonstrated a maximal proportion of telogen hairs at the end of summer.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors affecting hair growth include pregnancy, metabolic and genetic disorders, nutrition and seasonal changes. 9 Table 1 summarizes the published ranges for hair growth rates for different hair types. An average growth rate of 1 cm per month 4 is assumed for head hair.…”
Section: Hair Growthmentioning
confidence: 99%